2016
DOI: 10.3390/nu8090534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short-Term High-Nitrate Diet on Exercise Performance

Abstract: It has been reported that nitrate supplementation can improve exercise performance. Most of the studies have used either beetroot juice or sodium nitrate as a supplement; there is lack of data on the potential ergogenic benefits of an increased dietary nitrate intake from a diet based on fruits and vegetables. Our aim was to assess whether a high-nitrate diet increases nitric oxide bioavailability and to evaluate the effects of this nutritional intervention on exercise performance. Seven healthy male subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 45 publications
4
76
1
1
Order By: Relevance
“…Interestingly, in BR the time to exhaustion did not improve in 3 of 10 subjects, whereas it was remarkably higher in 5 of 10 subjects. This heterogeneity of results has been already reported by other authors both in healthy subjects (28) and in patients (43), and it has been shown to be correlated with changes of plasma [NO 3 Ϫ ] or [NO 2 Ϫ ] after supplementation. In our subjects, we did not observe any correlation between time to exhaustion and plasma [NO 3 Ϫ ].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Interestingly, in BR the time to exhaustion did not improve in 3 of 10 subjects, whereas it was remarkably higher in 5 of 10 subjects. This heterogeneity of results has been already reported by other authors both in healthy subjects (28) and in patients (43), and it has been shown to be correlated with changes of plasma [NO 3 Ϫ ] or [NO 2 Ϫ ] after supplementation. In our subjects, we did not observe any correlation between time to exhaustion and plasma [NO 3 Ϫ ].…”
Section: Discussionsupporting
confidence: 50%
“…Although relatively small, this amount could become a problem during long-term supplementation in the obese population. Future studies should therefore consider other sources of NO 3 Ϫ for chronic supplementations, such as nitrate-rich vegetables, as previously utilized in healthy subjects (28).…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ supplementation can enhance short-duration (Ͻ30 min) exercise performance (1,2,11,35,48). However, the efficacy of NO 3 Ϫ supplementation in improving longer duration exercise performance is less clear (6,11,12,34,57).…”
Section: Introductionmentioning
confidence: 99%
“…delivery, including simple sodium (28) or potassium salts (23), NO 3 --rich foods (44), 68 concentrated beetroot juice (BR) (58), and chard gel (GEL) (37,38 from the first blood sample until the 3.5 h sample, after which they were allowed to 151 sit at a desk, returning 30 min before the final sample. During the experimental trials,…”
Section: Introductionmentioning
confidence: 99%